Porto, A.(Ed.), Economía de la Educación Universitaria: Argentina - Brasil -Perú - Elías, Silvina (Estudios económicos, 2005)
Porto, A.(Ed.), Economía de la Educación Universitaria: Argentina - Brasil -Perú